Architecture and Visual Culture in the Age of AI: The Role of Generative Design - Pérez Nanclares, Carlos Mario; del Blanco García, Federico Luis (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This research explores the way in which platforms such as social media, along with generative design and artificial intelligence linked to computational design, have revolutionized the manner in which visual culture is produced, distributed, and consumed in the architectural field. This encompasses both the education in architecture and its practical application, giving rise to new ways of visual expression and the formation of new identities, both individual and collective.